2013
DOI: 10.3897/bdj.1.e1015
|View full text |Cite
|
Sign up to set email alerts
|

New country records of reptiles from Laos

Abstract: Four species of reptiles, of which one is represented by one of its subspecies, are recorded for the first time from Laos: Cyrtodactylus phongnhakebangensis, Lycodon futsingensis, and Lycodon ruhstrati, as Lycodon ruhstrati abditus, from limestone forests in Khammouane Province and Cyrtodactylus pseudoquadrivirgatus from hill evergreen forest in Salavan Province. These discoveries of lizards and snakes bring the total species number of reptiles to 189 in Laos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Also C. phongnhakebangensis from Vietnam and C. hinnamnoensis from Laos are generally very similar in morphology, which is the reason they were initially considered a single taxon (Luu et al 2013). However, our phylogenetic analyses show that C. phongnhakebangensis (Vietnam) is basal to the entire group of Cyrtodactylus species from Khammouane Province, Laos, including C. calamei and C. darevskii, with C. hinnamnoensis being the most distant relative (Fig.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Also C. phongnhakebangensis from Vietnam and C. hinnamnoensis from Laos are generally very similar in morphology, which is the reason they were initially considered a single taxon (Luu et al 2013). However, our phylogenetic analyses show that C. phongnhakebangensis (Vietnam) is basal to the entire group of Cyrtodactylus species from Khammouane Province, Laos, including C. calamei and C. darevskii, with C. hinnamnoensis being the most distant relative (Fig.…”
Section: Discussionmentioning
confidence: 80%
“…in Laos and Vietnam, respectively. Whereas cryptic diversity of Cyrtodactylus is already well documented in the Vietnamese side of that range (e.g., Ziegler et al 2010), only limited data is available from Laos (e.g., Nazarov et al 2014;Luu et al 2015a;Luu et al 2016a,b). Luu et al (2013) reported the first record of C. phongnhakebangensis in Laos, a species formerly only known from Phong Nha-Ke Bang NP in Vietnam. Here we provide more detailed morphological analysis in combination with molecular and ecological comparisons to show that the Laotian population in fact represents an undescribed cryptic species.…”
Section: Introductionmentioning
confidence: 99%
“…Between 2002 and 2010, our German–Vietnamese research team discovered and described 13 reptile taxa as ‘new to science’ from Phong Nha – Ke Bang National Park alone, and there is a considerably higher number of new provincial and country records of reptiles reported from this single forest site (Ziegler & Vu, ; Ziegler, ; Luu, Nguyen, Pham et al ., ). Although the project has now been handed over to the local Vietnamese cooperation partners, a PhD student continues herpetodiversity research on the other side of the border in the adjoining Hin Nam No National Protected Area in central Laos, where knowledge about the biodiversity is still limited (Luu, Nguyen, Calame et al ., ).…”
Section: In Situmentioning
confidence: 99%
“…Because of the heterogeneous habitat, tropical climate, forest, and watershed areas, it is rich in biodiversity. Altogether, 178 species of mammals, 740 species of birds, 189 species of reptiles, and 5,005 species of plants are reported to inhabit the Lao PDR ( IUCN 2007 ; Luu et al 2013 ; Zhu 2017 ; Avibase 2018 ). The biodiversity in the Lao PDR is exposed to several threats that have led to a decline in the native flora and fauna and the extinction of many species.…”
Section: Introductionmentioning
confidence: 99%